Eculizumab Salvage Therapy for Antibody‐Mediated Rejection in a Desensitization‐Resistant Intestinal Re‐Transplant Patient. Issue 7 (3rd February 2015) - Fan, J.; Tryphonopoulos, P.; Tekin, A.; Nishida, S.; Selvaggi, G.; Amador, A.; Jebrock, J.; Weppler, D.; Levi, D.; Vianna, R.; Ruiz, P.; Tzakis, A.
<x xml:space="preserve">Abstract</x> The presence of elevated calculated panel reactive antibody (cPRA) and anti‐HLA donor specific antibodies (DSA) are high risk factors for acute antibody‐mediated rejection (AAMR) in intestinal transplantation that may lead to graft loss. Eculizumab has been used for the treatment of AAMR in kidney transplantation of sensitized patients that do not respond to other treatment. Here, we report a case where eculizumab was used to treat AAMR in a desensitization‐resistant intestinal re‐transplant patient. A male patient lost his intestinal graft to AAMR 8.14 years after his primary transplant. He received a second intestinal graft that had to be explanted a month later due to refractory AAMR. The patient remained highly sensitized despite multiple treatments. He received a multivisceral graft and presented with severe AAMR on day 3 posttransplantation. The AAMR was successfully treated with eculizumab. The patient presently maintains an elevated cPRA level above 90% but his DSAs have decreased from 18 000 MFI (mean fluorescent intensity) to below the positive cut‐off value of 3000 MFI and remains rejection free with a 2‐year follow‐up since his multivisceral transplant. Eculizumab offers an alternative to treat AAMR in intestinal transplantation in desensitization‐resistant patients.